Continuum of hepatitis C care cascade in prison and following release in the direct-acting antivirals era - Sanam Hariri; Heidar Sharafi; Mahdi Sheikh; Shahin Merat; Farnaz Hashemi; Fatemeh Azimian; Babak Tamadoni; Rashid Ramazani; Mohammad Mehdi Gouya; Behzad Abbasi; Mehrzad Tashakorian; Ramin Alasvand; et al. (BMC, 2020)
Abstract Background People with criminal justice involvement contribute remarkably to the rising hepatitis C virus (HCV) burden; however, the continuum of care is a major barrier to prison-based programs. We aimed to evaluate a comprehensive HCV care model in an Iranian provincial prison. Methods Between 2017-2018, in the Karaj Central Prison, newly admitted male inmates received HCV antibody testing and venipuncture for RNA testing (antibody-positive only). Participants with positive RNA underwent direct-acting antiviral (DAA) therapy (Sofosbuvir/Daclatasvir). Sustained virological response was evaluated at 12 weeks post-treatment (SVR12). Results Overall, from 3485 participants, 182 (5.2%) and 117 (3.4%) tested positive for HCV antibody and RNA, respectively. Among 116 patients who were eligible for treatment, 24% (n = 28) were released before treatment and 72% (n = 83) initiated DAA therapy, of whom 81% (n = 67/83) completed treatment in prison, and the rest were released. Of total released patients, 68% (n = 30/44) were linked to care in community, and 70% (n = 21/30) completed treatment, including 60% (n = 12/20) and 90% (n = 9/10) among those who were released before and during treatment, respectively. The overall HCV treatment uptake and completion were 89% (n = 103/116) and 85% (n = 88/103), respectively. From people who completed treatment, 43% (n = 38/88) attended for response assessment and all were cured (SVR12 = 100%). Conclusions Integrated HCV care models are highly effective and can be significantly strengthened by post-release interventions. The close collaboration of community and prison healthcare systems is crucial to promote high levels of treatment adherence. Future studies should investigate the predictors of engagement with HCV care following release.